Legionella pneumophila: The Paradox of a Highly Sensitive Opportunistic Waterborne Pathogen Able to Persist in the Environment - Berjeaud, Jean-Marc; Chevalier, Sylvie; Schlusselhuber, Margot; Portier, Emilie; Loiseau, Clémence; Aucher, Willy; Lesouhaitier, Olivier; Verdon, Julien (Frontiers in Microbiology, 2016)
Legionella pneumophila, the major causative agent of Legionnaires’ disease, is found in freshwater environments in close association with free-living amoebae and multispecies biofilms, leading to persistence, spread, biocide resistance, and elevated virulence of the bacterium. Indeed, legionellosis outbreaks are mainly due to the ability of this bacterium to colonize and persist in water facilities, despite harsh physical and chemical treatments. However, these treatments are not totally efficient and, after a lag period, L. pneumophila may be able to quickly re-colonize these systems. Several natural compounds (biosurfactants, antimicrobial peptides…) with anti-Legionella properties have recently been described in the literature, highlighting their specific activities against this pathogen. In this review, we first consider this hallmark of Legionella to resist killing, in regard to its biofilm or host-associated life style. Then, we focus more accurately on natural anti-Legionella molecules described so far, which could provide new eco-friendly and alternative ways to struggle against this important pathogen in plumbing.